1986
DOI: 10.1080/00063658609476919
|View full text |Cite
|
Sign up to set email alerts
|

The diet of RavensCorvus coraxin Orkney

Abstract: An analysis of 945 pellets from various territories and communal roosts on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…However, nothing can be extrapolated from our observations regarding nonbreeding common ravens. Although one study found breeding and nonbreeding common raven diets to be similar during the spring (Marquiss and Booth 1986), further research that focuses on differences in predation rates of greater sage-grouse nests and food storage behaviors between breeding and nonbreeding common ravens is warranted. In addition, our study did not quantify the proportion of the population that exhibit behaviors of greater sage-grouse nest predation and caching eggs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, nothing can be extrapolated from our observations regarding nonbreeding common ravens. Although one study found breeding and nonbreeding common raven diets to be similar during the spring (Marquiss and Booth 1986), further research that focuses on differences in predation rates of greater sage-grouse nests and food storage behaviors between breeding and nonbreeding common ravens is warranted. In addition, our study did not quantify the proportion of the population that exhibit behaviors of greater sage-grouse nest predation and caching eggs.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our observations were merely opportunistic while conducting ecological studies that were not designed to actually locate common raven cache sites or to conduct behavioral investigations. Although we did not directly observe common ravens caching, retrieving or consuming the eggs, dietary investigations of breeding common ravens are often based on pellets, skeletal remains, and eggshells collected within the vicinity of nest sites (Marquiss and Booth 1986;Stiehl and Trautwein 1991). Investigations into the food storage behavior of the northwestern crow Corvus caurinus found that food was always eaten at the cache site, with the exception of clams, which were dropped onto nearby rocks (James and Verbeek 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most single methods of dietary analysis select for some charactenstic m a prey type which resists digestion (Hartley 1948, Pienkowski et al 1984 so an integration of methods is more accurate No major food items were identified from stomachs that did not also occur m pellets, which IS m agreement with the findings of Butler In the present study, drop sites were important in revealing prey items not recorded, or severely underrepresented, in pellets Expressing diet in terms of the frequency of occurrence can over-emphasize the importance of small prey items, though a large sample size tends to minimise this potential bias (Holyoak 1968, Marquiss pers comm ) The relative proportion of insects and gram declined from 38-54% of the diet to < 2%, when expressed as wet weight, due to the relatively low weight of these food items, but weight estimates can represent food items more accurately than can frequency occurrence The diet of hooded crows at Lough Hyne differed from that found in other studies on this species (Lockie 1956. Holyoak 1968, Houston 1977 in the large proportion of food gathered from the intertidal habitat Previous studies of the diet of corvids have shown that m-tertidal species may occur in 20-90% of raven Corvus corax L pellets (Ewms et al 1986, Marquiss andBooth 1986) or account for 40% of the total volume (Butler 1974) In a study of hooded crows in Argyll, Scotland, Houston (1977) beheved that the shore of Loch Feochan did not provide a good food source for crows due to competition from gulls Larus spp and the low food quality of the small gastropods and mussels they consumed Many of these studies relied on pellet and occasionally also stomach analysis to assess diet but little attention was paid to drop sites. Many bird species utilize specific sites to break open selected prey items (Morris 1954, Siegfried 1977 and the utilisation of drop sites by crows is widespread (Zach 1978, Richardson and Verbeek 1986, Whiteley et al 1990) Butler (1974 failed to account for drop sites in his analysis though they are used by crows in his study area (Richardson and Verbeek 1986) The present study shows that if a population of crows uses drop sites, failure to use the data available at these sites, in diet analysis, will result in considerable under-represention of some hardshelled prey items and furthermore may fail to record some important prey species Pellet analysis was sufficient to record those prey items not found at drop sites The dietary switch by hooded/carrion crows from soil invertebrates in the spring to grain and fruit in late summer and autumn has been well documented (Lockie 1956, Holyoak 1968…”
Section: Discussionmentioning
confidence: 84%
“…Hooded/carrion crows Corvus corone L are eurytopic in the British Isles occurring on farmland, moorland, in woodland and on the seashore (Sharrock 1976) Most previous dietary studies of Corvus corone concerned their feeding behaviour on agricultural land (Lockie 1956, Loman 1980, Waite 1984 or crow predation of game (Picozzi 1975, Loman and Goransson 1978, Erikstad et al 1982 A few have occasionally recorded the presence of intertidal species in the diet (Colhnge 1924, Holyoak 1968, Clegg 1972, Houston 1977 Elsewhere, studies on other Corvus species have shown that intertidal species may constitute an important part of the diet (Butler 1974, Marquiss andBooth 1986) and, as a consequence, influence the distribution of intertidal prey species (Zach 1978) Relatively few bird species occur on rocky shores (Feare and Summers 1986) but crows are known to prey on saxicolous species by dropping hard-shelled intertidal prey species onto hard surfaces e g road or rocky shore, m order to break them open (Zach 1978, Richardson and Verbeek 1986, Whiteley et al 1990 The abundance of sedentary ma-rine species on the shore changes little with season (Bayne 1976), yet the selection of bivalve and gastropod molluscs for dropping by crows occurs only dunng the winter (Houston 1977, Berrow et al 1991 Prey selection by birds may be influenced by many factors including the quahty of the prey and the bird's nutritional requirements (Moss et al 1972, Goss-Custard 1977 while weight loss by mussels during the winter has been shown to have a marked effect on the energy intake rate and size selection of mussels by oystercatchers Haematopus ostralegus L (Cayford and Goss-Custard 1990) Birds with strong prey preferences may be vulnerable to prey depletion since they are often incapable of switching to a more abundant food source (Dare andMercer 1973, O'Connor andBrown 1977) At Lough Hyne Marine Reserve, Co Cork, Ireland the possible impact of avian predators on marine invertebrates has been discussed by Ebling et al (1966) and Thain (1971) but there has been no attempt at quantification In order to assess the potential impact of avian pr...…”
Section: Introductionmentioning
confidence: 99%